The New Normal in Dental Education: Perceptions of E-Learning Among Dental Students and the Impact of the Pandemic on Education - Cengiz Evli; Gözde Haksayar (European Annals of Dental Sciences)
Dentistry education, unlike other professional programs, consists of three core components: theoretical education, laboratory (pre-clinical) practices, and clinical training. These components, along with various social programs, research projects, and interdisciplinary experiences, are highly integrated. With the global accessibility of the internet, especially during the COVID-19 pandemic, there has been a shift toward virtual learning across many fields. However, the unique structure of dentistry education has limited the widespread implementation of distance learning strategies.Aim and Method: This review aims to evaluate the perceptions of dentistry students regarding distance learning and in-class education, especially in the context of the COVID-19 pandemic. A detailed literature review was conducted, and relevant findings were summarized.Conclusion: Zhang et al.'s survey showed that 53.8% of students reported difficulty recalling material during distance learning, and 64.1% found it harder to concentrate compared to face-to-face lessons. Additionally, 79.5% experienced fatigue during online education. Despite challenges in practical training, students generally felt they had received adequate pre-clinical education. The pandemic impacted both learning and practical training, with students expressing fear of infection. Distance learning with interactive activities, quality materials, and well-organized modules can improve students' learning experiences and satisfaction, providing guidance for future educational models.